2016
DOI: 10.1160/th15-08-0692
|View full text |Cite
|
Sign up to set email alerts
|

Increased inhibitor incidence in severe haemophilia A since 1990 attributable to more low titre inhibitors

Abstract: Many studies have reported an increased incidence of inhibitors in previously untreated patients (PUPs) with severe haemophilia A after the introduction of recombinant products. It was the objective of this study to investigate whether the inhibitor incidence has increased between 1990 and 2009 in an unselected cohort of PUPs with severe haemophilia A (FVIII< 1 %). Patients were consecutively recruited from 31 haemophilia treatment centres in 16 countries and followed until 50 exposure days or until inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Table 4 denotes Patients showing Hemophilia A inhibitors. We sorted ten patients depending upon the clinical evidence of bleeding disorder, poor response to hemostatic therapy (Fischer et al, 2016) and patients experiencing more than 15 events /year to evaluate the ef icacy clotting capacity of Chromolena extract. Table 5 denotes FVIII assay in patients with inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Table 4 denotes Patients showing Hemophilia A inhibitors. We sorted ten patients depending upon the clinical evidence of bleeding disorder, poor response to hemostatic therapy (Fischer et al, 2016) and patients experiencing more than 15 events /year to evaluate the ef icacy clotting capacity of Chromolena extract. Table 5 denotes FVIII assay in patients with inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…The definition of a clinical important inhibitor, excluding single positive laboratory tests, has been proven to be of great importance. Overall more low-titre inhibitors have been detected [ 8 , 32 ]. Interestingly, many of the on-going large prospective observational studies, despite not having performed central testing, still have found very similar results for high-titre inhibitor incidences [ 2 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays it is recommended to test at least every 3 months for inhibitors during the first 50 EDs [ 31 ]. In a large study, the PedNet group divided all PUPs according to 5-year birth cohorts [ 32 ]. Over a 20-year period, inhibitor titres over a 20-year period where investigated in 926 PUPs with severe haemophilia.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 About 20% of children with SHA will have a high‐titer inhibitor and are in need of eradication treatment. 2 , 3 Inhibitors render FVIII replacement therapy ineffective, increasing the risk of morbidity and mortality. Immune tolerance induction (ITI) with repeated administration of FVIII is recommended as the only method for inhibitor eradication and would achieve 60% to 80% overall success rates.…”
Section: Introductionmentioning
confidence: 99%